Tuning the Anthranilamide Peptidomimetic Design to Selectively Target Planktonic Bacteria and Biofilm - Rajesh Kuppusamy; Muhammad Yasir; Tsz Tin Yu; Florida Voli; Orazio Vittorio; Michael J. Miller; Peter Lewis; David StC Black; Mark Willcox; Naresh Kumar (MDPI AG, 2023)
There is a pressing need to develop new antimicrobials to help combat the increase in antibiotic resistance that is occurring worldwide. In the current research, short amphiphilic antibacterial and antibiofilm agents were produced by tuning the hydrophobic and cationic groups of anthranilamide peptidomimetics. The attachment of a lysine cationic group at the tail position increased activity against E. coli by >16-fold (from >125 μM to 15.6 μM) and greatly reduced cytotoxicity against mammalian cells (from ≤20 μM to ≥150 μM). These compounds showed significant disruption of preformed biofilms of S. aureus at micromolar concentrations.